Effect of tree density on growth of rubber in North Eastern region of India - Dey S.K (Rubber Science, 2019)
A trial on planting density was conducted in clone RRII 429 with six densities viz 408, 445, 489, 544, 613 and 699 in rectangular planting. Growth of the plants was significantly influenced by the different densities sixth years after planting. The density up to 544 trees ha-1 attained required tappable girth by the end of seventh year. The percentage of tappable trees was low in the denser plantings. Plants at the lower density showed high girth increment in all the years. Seasonal variation in growth was observed. Highest girth increment was observed in monsoon season followed by post monsoon and lowest in winter season. Lower planting density produced higher tree girth and thick virgin bark.
Keywords: Growth; Hevea brasiliensis; North-East India; Planting density